Activation of the NLRP3 Inflammasome Pathway by Prokineticin 2 in Testicular Macrophages of Uropathogenic Escherichia coli- Induced Orchitis - Li, Ying; Su, Yufang; Zhou, Ting; Hu, Zhiyong; Wei, Jiajing; Wang, Wei; Liu, Chunyan; Zhang, Huiping; Zhao, Kai (Frontiers in Immunology, 2019)
Infections of the reproductive tract are known to contribute to testicular inflammatory impairment, leading to an increase of pro-inflammatory cytokines such as IL-1β and a decline in sperm quality. Prokineticin 2 (PK2), a secretory protein, is closely associated with the secretion of pro-inflammatory cytokines in inflamed tissue. It was reported that increased PK2 is related to the upregulation of IL-1β, but the underlying mechanism remains elusive. Here, we illustrated that PK2 was upregulated in testicular macrophages (TM) in a rat model of uropathogenic Escherichia coli (UPEC) infection, which induced the activation of the NLRP3 inflammasome pathway to boost IL-1β secretion. Administration of PK2 inhibitor alleviated the inflammatory damage and suppressed IL-1β secretion. Moreover, PK2 promoted NLRP3 expression and the release of cleaved IL-1β from TM to the supernatants after the challenge with UPEC in vitro. IL-1β in the supernatants affected Leydig cells by suppressing the expression of genes encoding for the enzymes P450scc and P450c17, which are involved in testosterone production. Overall, we revealed that increased PK2 levels in TM in UPEC-induced orchitis may impair testosterone synthesis via the activation of the NLRP3 pathway. Our study provides a new insight into the mechanisms underlying inflammation-associated male infertility and suggests an anti-inﬂammatory therapeutic target for male infertility.